(untitled) (Revista horizonte, 2013)
To prescribe and evaluate the intensity of aerobic exercise, percentages of heart rate (HR), maximal oxygen consumption (VO2 max), blood lactate concentrations, perceived exertion index, among others, have been used. perceived exertion index, among others. These physiological parameters have a certain relationship and one of them or an amalgam of them can be used. The relationship between HR and oxygen consumption (VO2) has long been established for submaximal (SM) and maximal aerobic exercise, with similar percentages between them. The indicator par excellence of aerobic exercise is VO2 max and its prediction can be made not only by means of a percentage of HR, but also by means of the post-exercise SM recovery heart rate (HRF). This form of prediction has been used in protocols of some validated tests and exposed in the literature. In this literature review, a series of investigations that have demonstrated the relationship between HRF and VO2 max will be presented. In the article, the behavior of HR and VO2 during aerobic exercise is presented, as well as the behavior of HR in recovery. Then, the relationship between both physiological parameters during and after aerobic exercise is shown, and then some tests that predict VO2 max from FCR are described. It is concluded that post-exercise SM FCR is a valid indicator to estimate VO2 max, and that these parameters are inversely proportional.